Addition of Pulses, Cooking Oils, and Vegetables Enhances Resistant Starch and Lowers the Glycemic Index of Rice (Oryza sativa L.). (11th February 2020) - Kumar, Awadhesh; Panda, Puja Archana; Lal, Milan Kumar; Ngangkham, Umakanta; Sahu, Chandrasekhar; Soren, Khela Ram; Subudhi, Hata Nath; Samantaray, Sanghamitra; Sharma, Srigopal
Abstract: Rice exhibits relatively high glycemic index (GI) value compared to other carbohydrate rich foods. Eating rice as a staple food and leading sedentary life style may lead to obesity and type‐II diabetes. National Rice Research Institute (ICAR‐NRRI), Cuttack, India released varieties were analyzed for low GI and high resistant starch (RS) content. Large variations were observed in the GI (57.5–76.4) and RS content (0.28–2.94%) among the varieties. The rice Shaktiman had the lowest GI (57.50) with relatively high RS content (2.11%) while Gayatri had the highest RS (2.94%) with relatively low GI (60.31) value. Addition of pigeon pea to rice resulted in lowering of GI and increased RS content compared to other pulses. Addition of ghee (clarified butter) to rice during cooking resulted in lowering of GI and increase in RS content. The effect was not so pronounced with vegetable oils. Addition of vegetables like fenugreek and cauliflower to rice caused much more lowering of GI as compared to other vegetables. The findings emphasize the importance of identifying and developing rice with low GI and high RS content. This also highlights the importance of formulating food combinations of rice with other edible commodities that suit diabetics. Abstract : Rice exhibits a relatively high glycemic index (GI) value compared to other carbohydrate rich foods. National Rice Research Institute (ICAR‐NRRI), Cuttack, India released varieties are analyzed for low GI and high resistant starch (RS) content. Large variations were observed in the GI (57.5–76.4) and RS content (0.28–2.94%) among the varieties.